Milk kefir enriched with inulin‐grafted seed extract from white wine pomace: chemical characterisation, antioxidant profile and in vitro gastrointestinal digestion. (4th April 2022) - Carullo, Gabriele; Spizzirri, Umile Gianfranco; Montopoli, Monica; Cocetta, Veronica; Armentano, Biagio; Tinazzi, Mattia; Sciubba, Fabio; Giorgi, Gianluca; Enrica Di Cocco, Maria; Bohn, Torsten; Aiello, Francesca; Restuccia, Donatella
Summary: An innovative functional food with symbiotic and functional potential was produced by combining probiotic milk kefir, and white grape‐seed pomace obtained by UAE (ultrasound‐assisted extraction) rich in catechin and glycosylated flavonoids. The milk kefir was fortified by adding, after 24 h of fermentation, a polymer of inulin grafted with seed extract. The inulin/grape extract‐enriched polymer showed a higher antioxidant profile ( P  < 0.05). Simulated in vitro digestion demonstrated that 50 g of the kefir product would result in the delivery of antioxidants equivalent to 300 mg of ascorbic acid. The integrity of the intestinal barrier functions was not compromised by kefir treatments (at 10 μg mL ‐1 ). Abstract : Seeds from white wine pomace furnished an extract rich of valuable phytochemicals. This extract was grafted to Inulin and added as functional ingredient during the preparation of milk kefir. This enriched milk kefir was assayed in vitro about its antioxidant profile and bioaccessibility.